The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15252/embj.201592534
|View full text |Cite
|
Sign up to set email alerts
|

Inducible chromatin priming is associated with the establishment of immunological memory in T cells

Abstract: Immunological memory is a defining feature of vertebrate physiology, allowing rapid responses to repeat infections. However, the molecular mechanisms required for its establishment and maintenance remain poorly understood. Here, we demonstrated that the first steps in the acquisition of T‐cell memory occurred during the initial activation phase of naïve T cells by an antigenic stimulus. This event initiated extensive chromatin remodeling that reprogrammed immune response genes toward a stably maintained primed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
239
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(266 citation statements)
references
References 57 publications
(136 reference statements)
21
239
0
Order By: Relevance
“…Recently, Bevington et al . uncovered the presence of stably maintained DNase-hypersensitive sites in the murine memory T cells42 which further supports our findings. Here we report that in human memory T cells positive chromatin modifications are also present in the vicinity of rapid recall genes.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Bevington et al . uncovered the presence of stably maintained DNase-hypersensitive sites in the murine memory T cells42 which further supports our findings. Here we report that in human memory T cells positive chromatin modifications are also present in the vicinity of rapid recall genes.…”
Section: Discussionsupporting
confidence: 89%
“…In line with our observation, a recent paper studying long-term memory in primary macrophages concluded that removal of repressive H3K9 methylation enabled transcriptional memory induced by LPS exposure (35). In future studies, it will be interesting to survey the nucleosome landscape to query whether nucleosome depletion occurring during Pol II elongation is another event that is inherited, as suggested in recent studies of transcriptional memory in mammalian cells (6,7).…”
Section: Discussionsupporting
confidence: 86%
“…In silico analyses of common transcription factor binding motifs revealed the presence of consensus NFAT binding motifs in the regulatory regions of Slc2a1 , Slc2a3 , Hk2, Aldoa, Pgk1, Eno1 as well as Myc, Irf4 and Hif1a . Analysis of DNase I hypersensitivity (Bevington et al, 2016) and ATAC-sequencing (Mognol et al, 2017) data from naïve and activated CD8 + T cells revealed open chromatin regions in the regulatory regions of Irf4, Slc2a3 (Figure 5A) as well as Hif1a, Myc, Slc2a1 and Hk2 (Figure S5A). To determine if NFAT binds to these open chromatin regions, we analyzed genome-wide ChIP-sequencing (ChIP-seq) data that report on the binding of NFATc2 in WT (and Nfatc2 -deficient) CD8 + T cells (Martinez et al, 2015) and NFATc1 in activated CD8 + T cells from a NFATc1 BAC-transgenic mouse line (Klein-Hessling, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…NFATc2 ChIP-seq data (Martinez et al, 2015) and genome-wide NFATc1 chromatin binding data (using T cells from a BAC-transgenic mouse strain in which NFATc1 is endogenously biotinylated by the biotin-ligase BirA and precipitated using streptavidin beads) (Klein-Hessling, 2017) were aligned to open chromatin regions defined by DNase I hypersensitivity sites in naïve and CD8 + T cell blasts (Bevington et al, 2016) and accessible chromatin regions defined by ATAC-seq in resting and PMA/ionomycin-stimulated CD8 + T cells (Mognol et al, 2017). All sequencing data was mapped to the mouse mm9 genome assembly using the Bowtie software package.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation